Antibacterial activity of ethanolic extracts from Zingiber zerumbet rhizome against Salmonella spp. - Imbang Dwi Rahayu; WAHYU WIDODO; INDAH PRIHARTINI; ARIS WINAYA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahayu ID, Widodo W, Prihartini I, Winaya A. 2019. Antibacterial activity of ethanolic extracts from Zingiber zerumbet rhizome against Salmonella spp. Biodiversitas 20: 3322-3327. The study aimed at investigating the antibacterial activity of ethanolic extracts of the Lempuyang Gajah (Zingiber zerumbet (L.) Smith) rhizome against Salmonella enteritidis ATCC 31194 and S. typhimurium ATCC 23564. An experimental method was employed for testing the antibacterial activity, with a completely randomized design (CRD) of factorial patterns. Factor I, ethanol concentrations which consisted of 45%; 70% and 95%, while factor II was the concentration of extracts, i.e 0%; 2.5%; 5%; 7.5% and 10%. The phytochemical screening results showed that the Z. zerumbet extracts with 45% and 70% ethanol, contained alkaloids, tannins, terpenoids, and saponins; however, the-95%-ethanol did not result in any saponins, but flavonoids instead. Meanwhile, the chromatogram patterns of all extracts showed zerumbone is a dominant compound. Extraction of Z. zerumbet using 95% ethanol has higher antibacterial activity against S. enteritidis than S. typhimurium. The extract with 10% concentration gave the highest antibacterial activity than other concentrations. It can be concluded that the Z. zerumbet L. Smith extracts with 95% ethanol and 10% concentration has the best antibacterial activity against S. enteritidis. Whereas S. typhimurium is effectively inhibited by extracts with 45% ethanol and 7.5% extract concentration.